EFFORTS TO DEVELOP SOCIAL-EMOTIONAL ASPECTS IN SHOWING TOLERANCE USING A COMBINATION OF EXPLICIT INSTRUCTION MODEL AND COOPERATIVE LEARNING WITH PLAYING METHOD IN EARLY CHILDHOOD EDUCATION STUDENT’S - Mayasari, Mayasari; Asniwati, Asniwati (Indonesian Researcher Society for Science Technology and Education (IDREST) Publisher, 2018)
The result and process of learning of at early childhood education children are still not in accordance with their age and expectation that faced by the low of social-emotional development specifically on tolerance and cooperation in conducting during various teaching and learning activities. In order to solve the problem, this study used the combination of explicit instruction and cooperative learning model with playing method. This research was conducted using qualitative approach with class action research and three times learning class and using instrument to observe of teacher and students? activities. The result indicates that the teacher and children activities improved on the third learning with very good and very active criterion, and children social-emotional aspect develop gradually as expected at the last learning.